Evolution of Caste System: How are Nepali Dalits Left Behind in Education? - Chalaune, Bhawan Singh (Scholars' Journal, 2022)
The purpose of this article is to explore the reasons behind the historical backwardness of Dalits in education and analyze it on a theoretical basis. Based on theoretical review and personal interactions, this article is qualitative. Due to the strict policy of the caste system, especially Dalits have been deprived of every opportunity of human development for a long time. Manusmriti gave untouchability to the caste system which started from the Varna system in the name of religion. The ruler of the state merged religion with the state. Thus historically Dalits have been deprived of education by both religion and the state. At present, despite the removal of caste restrictions, the participation, sustainability, and achievement of Dalits in education are low. Even though the state has provided various facilities by increasing educational opportunities, there has been no meaningful participation of Dalit children in schools. The main reason for this is the continuity of social culture and the ceiling of job. The caste discrimination in the community is reflected in the schools as well. As a result, Dalit children have not been able to take benefit from the current education system in a fair and independent manner. This article shows that Dalits can be brought into the mainstream of education only through the education system which can create an equitable cultural capital to change the social structure developed on the cultural basis of inequality. Similarly, the education system needs to be restructured, and continuous efforts are needed to transform discriminatory values and attitudes into human values and integrate these values into practice.